Spectral induced polarization survey for the estimation of hydrogeological parameters in an active rock glacier - C. Moser; U. Morra di Cella; C. Hauck; A. Flores Orozco (The Cryosphere)
Degrading permafrost in rock glaciers has been reported from several sites in the European Alps. Changes in ground temperature and ice content are expected to affect the hydrogeological properties of rock glaciers and in turn modify the runoff regime and groundwater recharge in high-mountain environments. In this study, we investigate the use of an emerging geophysical method in permafrost studies to understand the hydrogeological properties of the active Gran Sometta rock glacier, which consists of a two-lobe tongue (a white and a black) whose lobes differ in their geologies. We present the application of spectral induced polarization (SIP) imaging, a method that provides quasi-continuous spatial information about the electrical conductivity and polarization of the subsurface, which are linked to hydrogeological properties. To quantify the water content and the hydraulic conductivity from SIP imaging results, we used the petrophysical dynamic stern layer model. The SIP results show a continuously frozen layer at 4–6 m depth along both lobes which hinders the infiltration of water, leading to a quick flow through the active layer. To evaluate our results, we conducted tracer experiments monitored with time-lapse electrical conductivity imaging, which confirms the hydraulic barrier associated with the frozen layer and allows the pore water velocity to be quantified (∼ 10−2 m s−1). Below the frozen layer, both lobes have distinct water content and hydraulic conductivity. We observed a higher water content in the black lobe, which moves faster than the white lobe, supporting the hypothesis that the water content at the shear horizon affects the rock glacier velocity. Our study demonstrates that the SIP method is able to provide valuable information for the hydrogeological characterization of rock glaciers.